Content validity by expert judgment of the NIOSH Worker Well-Being Questionnaire in Spanish for measuring Well-being in wildfire fighters in Mexico: Validez de contenido por juicio de expertos del NIOSH Worker Well-Being Questionnaire en Español para medir el Bienestar en combatientes de incendios forestales en México - Alcaraz Sánchez, Esmeralda (2024)
Introduction: Firefighting in forests is a dangerous and demanding task, highlighting the need to understand the well-being of these workers through tools such as the NIOSH Worker Well-Being Questionnaire  in Spanish. However, this questionnaire has not been adapted and validated for the Mexican context. Objective: The study aimed to validate the NIOSH Worker Well-Being Questionnaire in Spanish for forest firefighters in Mexico. Methods: A psychometric design was used, including content validation through expert judgment in validation, health, and work activities related to firefighting. The questionnaire incorporates five domains with a Likert scale, and the Aiken's V coefficient was used for validation. Results: Most items in the questionnaire showed an Aiken's V coefficient above 0.70, with 95% confidence intervals, indicating high content validity. There was concordance with the original validation of the instrument, enabling its application in the Mexican work context. Conclusion: The expert validation confirmed the relevance, coherence, and clarity of the NIOSH Worker Well-Being Questionnaire in Spanish for forest firefighters in Mexico. This analysis is a critical component of a broader project, laying the groundwork for subsequent stages including a pilot test and factorial analysis, as well as contributing to improving the safety and quality of life of these workers.